Desquamative interstitial pneumonia complicated by diffuse alveolar haemorrhage. Issue 2 (22nd December 2017) - Matsuo, Ayako; Matsumoto, Nobuhiro; Kitamura, Akiko; Tsubouchi, Hironobu; Yanagi, Shigehisa; Nakazato, Masamitsu
Abstract : We report a rare case of desquamative interstitial pneumonia (DIP) with diffuse alveolar haemorrhage (DAH). A 56‐year‐old man diagnosed with DIP by surgical lung biopsy 2 years ago was admitted to our hospital because of severe acute respiratory failure. The DIP had progressed despite smoking cessation. On admission, the patient appeared extremely ill, and physical examination revealed respiratory distress. The patient required mechanical ventilation. High‐resolution computed tomography showed diffuse ground glass opacity in both lungs. The bronchoalveolar lavage fluid was bloody, and numerous haemosiderin‐laden alveolar macrophages were detected. Pulse steroid therapy followed by oral prednisolone immediately relieved the respiratory failure and improved the long‐term control of the DIP. Paired sera tests confirmed the diagnosis of influenza A/H3N2 virus infection, which was the cause of the DAH. Chronically progressive DIP with acute respiratory failure due to DAH was successfully treated by steroid therapy. Abstract : We report a rare case of desquamative interstitial pneumonia (DIP) with diffuse alveolar haemorrhage (DAH). The DIP of this case was not improved by smoking cessation and the patient's exercise capacity deteriorated gradually. The DAH, which was caused by influenza infection, worsened his respiratory condition. Pulse steroid therapy followed by oral prednisolone immediately relieved the patient's respiratory failure and the long‐term control of the DIP.